2008
DOI: 10.1159/000182816
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in African-Americans vs. Caucasians Using Thymoglobulin or Interleukin-2 Receptor Inhibitor Induction: Analysis of USRDS Database

Abstract: Aim: We used the USRDS database to test the hypothesis that graft survival was similar using either rabbit antithymocyte globulin (rATG) vs. interleukin-2 receptor inhibitor (IL2i) in the Prograf era. We further explored the variable of race in the two groups of patients. Methods: We conducted a retrospective cohort study of kidney transplant patients in the USRDS from 2000 through 2005 to compare graft survival (including death) using rATG vs. IL2i with particular reference to outcomes between African-America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Our study also included a 10-year contemporary cohort with substantially longer follow-up, thus allowing for improved power to assess the impact of cytolytic induction therapy on long-term graft survival. 35 Jindal et al 14 analyzed transplant registry data in a 2009 publication, demonstrating that rATG use, as compared with IL-2RA induction therapy, was associated with a nonstatically significant reduction in the risk of graft loss in AAs (aHR 0.95, 95% CI 0.87–1.04). The population of AAs in the Jindal study was 58% smaller (n = 10,568) and had substantially shorter follow-up, as compared with our analysis, which is likely why they were unable to demonstrate a significant difference in long-term patient and graft outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also included a 10-year contemporary cohort with substantially longer follow-up, thus allowing for improved power to assess the impact of cytolytic induction therapy on long-term graft survival. 35 Jindal et al 14 analyzed transplant registry data in a 2009 publication, demonstrating that rATG use, as compared with IL-2RA induction therapy, was associated with a nonstatically significant reduction in the risk of graft loss in AAs (aHR 0.95, 95% CI 0.87–1.04). The population of AAs in the Jindal study was 58% smaller (n = 10,568) and had substantially shorter follow-up, as compared with our analysis, which is likely why they were unable to demonstrate a significant difference in long-term patient and graft outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54][55][56] Induction agents work to deplete the T-and B-cell stores or interfere with the adaptive immune response at the time of alloantigen presentation with transplantation. Induction consists of a polyclonal or monoclonal antibody against thymocytes such as thymoglobulin and alemtuzumab.…”
Section: Immunosuppressionmentioning
confidence: 99%
“…Induction consists of a polyclonal or monoclonal antibody against thymocytes such as thymoglobulin and alemtuzumab. [52][53][54][55][56] This approach has reduced the need for long-term steroid use and the associated cardiovascular risk factors. 57 Once transplantation has taken place, maintenance therapy begins with triple-drug therapy.…”
Section: Immunosuppressionmentioning
confidence: 99%
“…Evaluation of data from the United States Renal Data System from 2000 to 2005 showed that the frequency of patient survival and frequency of graft survival were similar in white and black patients who had induction with ATG or IL-2R antibodies. 32 Induction Agents: Discontinued and Investigational Agents efalizumab Efalizumab (Raptiva, Genentech, San Francisco, CA, USA) functions as an immunosuppressant by binding to the CD11a subunit of lymphocyte function-associated antigen 1 and inhibiting white blood cell migration. Efalizumab was indicated for the treatment of chronic moderate-to-severe plaque psoriasis.…”
Section: Induction Agents: Nondepleting Antibodiesmentioning
confidence: 99%